1993
DOI: 10.1029/92jd01910
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ozone with NOy in photochemically aged air

Abstract: During the summer of 1988, measurements of photochemical trace species were made at a coordinated network of seven rural sites in the eastern United States and Canada. At six of these sites concurrent measurements of ozone and the sum of the reactive nitrogen species, NOy, were made, and at four of the sites a measure for the reaction products of the NO x oxidation was obtained. Common to all sites, ozone, in photochemically aged air during the summer, shows an increase with increasing NOy levels, from a backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
225
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(242 citation statements)
references
References 33 publications
13
225
1
3
Order By: Relevance
“…Observation-based studies of O3, its precursors, and other tracers of continental emissions provide useful information on background levels as well as evidence of intercontinental influence on these concentrations (2,13,(18)(19)(20)(21). In fact, O3 observations at mountain sites in Europe indicate that human activities over the past century have at least doubled tropospheric O3 concentrations (22).…”
Section: Evidence For Ict Of Air Pollutionmentioning
confidence: 99%
“…Observation-based studies of O3, its precursors, and other tracers of continental emissions provide useful information on background levels as well as evidence of intercontinental influence on these concentrations (2,13,(18)(19)(20)(21). In fact, O3 observations at mountain sites in Europe indicate that human activities over the past century have at least doubled tropospheric O3 concentrations (22).…”
Section: Evidence For Ict Of Air Pollutionmentioning
confidence: 99%
“…Since NO y is representative of all NO x emissions, NO z provides a measure of the number of NO x molecules that have undergone photo-oxidation. Several studies have shown that the O 3 abundance in polluted air masses is linearly related to the abundance of NO z (e.g., Trainer et al, 1993;Kleinman, 2000). The enhancement of O 3 abundance relative to NO z (i.e.…”
Section: Plume Photochemistrymentioning
confidence: 99%
“…The OPE x can be derived from the regression slopes of correlations between O x and NO z [Kleinman et al, 1994;Trainer et al, 1993]. Therefore, the accuracy of NO 2 measurement plays an important role in the calculation of OPE x by influencing the quantification of O x and NO z .…”
Section: Ozone Production Efficiency (Ope X )mentioning
confidence: 99%
“…Since the oxidants of NO x can be removed from the O 3 -productionreaction system, Liu et al [1987] defined the number of molecules of O 3 formed per NO x as O 3 production efficiency of NO x (OPE x ), which has been used as an important indicator in studying O 3 chemistry. Trainer et al [1993] and Kleinman et al [1994] found better correlations between O 3 and the oxidation products of NO x , i.e., NO z (= NO y À NO x ) than the sum of reactive nitrogen species, NO y , in the photochemically aged air, based on which the OPE x was revised as Δ[O 3 + NO 2 ] / Δ[NO z ]. Therefore, accurate measurements of NO y and NO x are of importance to understand the formation mechanism of O 3 production, and hence to make the corresponding control strategies for mitigation of photochemical smog.…”
Section: Introductionmentioning
confidence: 99%